Data Dependence and Existence and Uniqueness for Hilfer Nabla Fractional Difference Equations (Contemporary Mathematics, 2024)
In the present article, we establish sufficient conditions for the existence of a unique bounded solution using a prominent fixed-point theorem for the non-linear initial value problem involving the recently introduced Hilfer nabla fractional difference operator.where 0
Keywords: Hilfer nabla fractional difference; initial value problem; existence; uniqueness; Ulam-Hyers stability